2022
DOI: 10.2147/jir.s380642
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Leptin as Biomarkers of Disease Activity and Metabolic Disorders in Rheumatoid Arthritis Patients

Abstract: Background Rheumatoid arthritis (RA) is an autoimmune disease, characterized by inflammation of multiple joints, resulting in irreversible cartilage and bone destruction. Chronic disease activity may be associated with metabolic disorders and premature atherosclerosis. Adipokines are involved not only in metabolism regulation, but also in inflammatory and immune response. Aim This study is designed to explore relationships between adipokines (adiponectin, leptin) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Comparable results were reported in a study focused on the role of adipokines in RA [8]. Unchanged concentrations of leptin and adiponectin remains unchanged even after two years of observation [54]. One of the limitations of this study is that participating patients had a healthy glucose or lipid metabolism even before bDMARDs treatment initiation, at least based on the parameters measured.…”
Section: Discussionmentioning
confidence: 52%
“…Comparable results were reported in a study focused on the role of adipokines in RA [8]. Unchanged concentrations of leptin and adiponectin remains unchanged even after two years of observation [54]. One of the limitations of this study is that participating patients had a healthy glucose or lipid metabolism even before bDMARDs treatment initiation, at least based on the parameters measured.…”
Section: Discussionmentioning
confidence: 52%
“…However, recent studies in human chondrocytes have shown that these cells can produce leptin and express its long receptor, suggesting that this molecule may have a local function [208]. While some studies have reported a correlation between circulating leptin levels and disease activity markers such as C-reactive protein (CRP) and DAS28 [82,205,209,213,218,223,[226][227][228][229][230][231][232][233], not all investigations support these associations [220,222,224]. In their metaanalysis, Lee et al [82] concluded that a modest yet statistically significant correlation exists between leptin levels and disease activity parameters such as DAS28 and CRP.…”
Section: Leptinmentioning
confidence: 99%
“…Leptin is one of the key markers of adipose tissue metabolism and energy metabolism [5]. At the same time, it is regarded as a proinflammatory adipokine since it stimulates the production of proinflammatory cytokines (TNF-α, IL-6), CC-chemokines, favors the Th1 phenotype in the Th1/Th2 balance, and correlates with the C-reactive protein level [5,6]. The results showed that chronic cold stress leads to a significant increase in leptin serum level (Table 1).…”
mentioning
confidence: 99%